Study Effect of Breed on Milk Production Traits and their Regression on Weight in Local and Cypriot Goats - Doha Salah Jameel; Abdallah Hameed Salim (University of Thi-Qar Journal of agricultural research, 2024)
The study was conducted on a group of goats in the Ruminant Research Station of the Agricultural Research Department. It aimed to study the effect of breed on milk production and its components, which include (daily milk production, milk protein percentage, milk fat percentage, milk lactose percentage and non-fat solids percentage) in both local and Cypriot goats, and to study correlation and regression coefficient between studied traits, for effect of goat breed (local and Cypriot) on milk production traits and its components. The results indicated that there were no significant differences between two breeds with respect to trait (total milk production, number of milking days, peak production, fat percentage and protein percentage). Also noted that local goats superiority Cypriot goats in trait of total milk production, number of milking days, peak production and protein percentage. As for trait of fat, and noted that Cypriot goats superiority local goats. The results indicated that there were highly significant differences (P≤0.01) with respect to the lactose trait, with local goats superiority Cypriot goats. There were also significant differences (P≤0.05) between two breeds for non-fat solids trait with superiority of local goats over Cypriot goats, most of correlations between studied traits were significant and medium to highly correlated and regression coefficient of these traits on birth weights, weaning and current weights were not significant at all levels of significance studied.